(untitled) (Journal of the College of Basic Education, 2022)
The Current Search in tersest in the Study of Female Body,& its shifts that which occur within the technical& aesthetic Side,& the shifts way of the Female Body by the way of format which called to framing Mesopotamian pottery work. The Searcher tries in this Search, to focusing on the shift theory, that which determined by using technology to emerge the painted Female Body that added on the ancient Mesopotamian ceramic pots. So, the problem of the search that Specified in the first chapter was the Female Body by change & Shift & the technical Style is the result of the Potter artist mind & his sense as a twisted system in his internal structure. Hence, It is not Possible for the transitions to happen on the reasonableness alone, ok on the noticeability a lone, So, the changeable is multi- shapes in quality & quantity changeful. It is possible to be by technical for the new Female Body which added on the Ceramic, which his shapes intervene with Some Portraits, Whether it was Vegetarian or animals shape. Considering the role that the Shifts Played to be distinctive factor for expressing at all human activities that which Ceramic be used in it. In other words, the Importance of the use is not restricted in spec: flying the traditional meaning, but also in all human activities. The Importance of the Search emerges at the Possibility to regard this study as addition from the specialized researcher side& the Scholar in this field. In Contrast, We should tackle past & the Impact toward modernity, that the Shift theory caring for it & to guarantee material for philosophical remedy for new artistic language. The Current Search aims to: The detection about the technological shifts for Female Body that drawn & added on the Mesopotamian Ceramic pots. The Work on diagnosis& display the beautified features for Female Body through the ancient Mesopotamian Pottiry artistic production. The Current Search is Specified in the Study, detection& Work on diagnosis& display the beautified features for Female Body through shifts on Ceramic, that Specified on four Ceramic Stages; Hasson Ceramic, Samara, Hale f, & Al- Aabeed. The period before writing Stage. It is made by different ores& multiple techniques styles. The researcher specifies a number of terms which include the search. The Second chapter include the theoretical from that Contains three Sections as the following: The first Section: The language of shift for female body The Second section: The aesthetic features for guided shift of female body. The third Section: The movement of ancient Mesopotamian pottery industries & the female shapes that painted on Ceramic. On the third chapter there were the procedures of the search which Contain the search Community & its Sample which reaches four Samples from the samples for the Ceramic roles from before writing age. Depending on descriptive analytical method, in accordance to shifting study. In the fourth chapter, the researcher reaches to the Search results, by depending on foreign Arabic Study Sources.